Novel Clinical and Genomic Signatures of the 2022 Monkeypox Virus - Meng-Xu Sun; Xing-Yao Huang; Cheng-Feng Qin (Zoonoses)
The monkeypox outbreaks started in 2022 and became an unexpected public health emergency of international concern (PHEIC). The factors that drove this neglected zoonosis in Africa into a global focus is largely unknown. Combined clinical, epidemiologic, and phylogenomic analyses indicate that substantial genome mutations, deletions, and rearrangement contributed to the sudden outbreak and unusual features in transmission and outcomes. Because no vaccine or antiviral drug is available in China, we call for immediate action and collaboration in response to the new monkeypox crisis.